Effect of lunging exercise program with Pessoa training aid on cardiac physical conditioning predictors in adult horses - R.F. Siqueira; M.S. Teixeira; F.P. Perez; L.S. Gulart (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2023)
ABSTRACT The aim of this study was to evaluate the effect the Pessoa training aid (PTA) exercise program exerts in some physical conditioning predictors. Eight detrained adult horses were evaluated in 12 sessions of work with PTA (3 sessions per week). All horses used a heart rate monitor and GPS (V800, Polar Electro) and data was used to calculate energy expenditure (EE), net cost of transport (COT), metabolic energy requirement (Pmet), oxygen pulse, oxygen utilization, heart rate and heart rate variability (HRV). The horses were weighted, and the thoracolumbar shape were measured at the level of the 18th (T18), 13th (T13) and 8th (T8) thoracic vertebrae with a flexible ruler before and after the experimental period. Data obtained weekly were submitted to ANOVA and Tukey test (p≤0.05). Data obtained just before and after the experimental period were submitted to paired t test. There was a decrease in left-right asymmetry. In the third week there was an increase in HR, EE, oxygen pulse and oxygen utilization followed by a decrease in the fourth week. The biomechanics related parameters, COT and Pmet decreased week by week. The HRV showed a sympathetic stimulus in the third week followed by a shift to parasympathetic in the fourth week. We conclude that 12 sessions of lunge exercise with PTA contributed to physical condition improvement.